A Rare Case of Complete Fragmentation of Pacemaker Lead after a High-Velocity Theme Park Ride. (18th October 2018) - Khattak, Furqan; Khalid, Muhammad; Gaddam, Sathvika; Ramu, Vijay; Brahmbhatt, Vipul
Abstract : Pacemaker lead fracture is one of the most common causes of pacemaker malfunction and is most frequently associated with weight lifting or chest trauma. These patients usually present with symptoms of dizziness, syncope, chest discomfort, and palpitations or less commonly with extracardiac symptoms. Diagnosis is made by ECG and careful review of chest imaging such as chest X-ray or fluoroscopy. Treatment involves placement of a new lead with or without extraction of the fractured lead. We present an interesting case of complete severance of the tip of a dual-chamber pacemaker's atrial lead after a high-velocity theme park ride. In our case, the fracture occurred during amusement park rides and went undiagnosed until the patient presented for routine pacemaker evaluation. This case indicates that extreme physical forces in the absence of direct trauma, such as during amusement park rides, may result in lead fractures and patients with pacemakers should be cautioned regarding such activities.